151 A Study of Erectile Dysfunction in Men 40 Years of Age or Younger. (1st May 2022) - Yamagishi, M.; Sasaki, H.; Ogushi, Y.; Niikura, A.; Ota, T.; Ichimura, Y.; Hashimoto, Y.; Sugishita, H.; Kurokawa, I.; Tanifuji, S.; Imamura, Y.; Shimoyama, H.; et al.
ABSTRACT: : In recent years, awareness of erectile dysfunction and the demand for treatment have been increasing even among young men. We investigated the status of young patients 40 years of age or younger with erectile dysfunction. The subjects were 208 patients who visited the urology departments of Showa University Fujigaoka Hospital and affiliated hospitals with a chief complaint of erectile dysfunction. The erectile function was assessed with the Sexual Health Inventory for Men (SHIM), diary questions on sexual intercourse from the Sexual Encounter Profile, and the Erection Hardness Score, which measures the hardness of erection. The treatment was monotherapy with sildenafil (25 or 50 mg), vardenafil (10 or 20 mg), or tadalafil (10 or 20 mg) or a combination of multiple phosphodiesterase 5 (PDE5) inhibitors. To investigate the cause, blood tests including free testosterone and the Self-rating Depression Scale questionnaire were conducted, and Pulse Wave Velocity (PWV) was measured. The median age of the patients was 36 years. As for the cause of erectile dysfunction, psychogenic erectile dysfunction was observed in 141 patients, accounting for 67.7% of the patients. However, 82.1% of patients who underwent PWV measurement showed measurements suggestive of organic changes. The efficacy rates of PDE5 inhibitors were 77% for sildenafil, 73% for vardenafil, and 85% for tadalafil. This study showed that psychogenic erectile dysfunction was common in young patients, and that PDE5 inhibitors were effective for them. In addition, the study suggested the presence of organic changes as a risk factor for erectile dysfunction even in young patients. Disclosure: Work supported by industry: no.